(untitled) (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2025)
This study investigates the effectiveness of Alphabet Busy Picture media in improving early childhood letter-recognition skills at PAUD Zalfa Naqiyya Samarinda. Addressing the urgent need for engaging literacy strategies in early education, this research offers a novel application of Busy Picture media to strengthen children’s alphabet mastery. Using a quantitative approach supported by classroom observations and interviews, the study involved 16 Class A students across two meetings. Early literacy development—especially letter recognition and identifying initial letters of familiar objects—is essential for foundational reading skills. Findings demonstrate that Alphabet Busy Picture media significantly enhanced students’ ability to recognize and memorize letters. The practical and visually stimulating nature of the media contributed to increased student engagement and learning outcomes. This research contributes empirical evidence supporting the integration of interactive visual media in early childhood literacy instruction, particularly for improving alphabet mastery in similar educational contexts.